If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 8) = 6x + 3 Reorder the terms: x(8 + x) = 6x + 3 (8 * x + x * x) = 6x + 3 (8x + x2) = 6x + 3 Reorder the terms: 8x + x2 = 3 + 6x Solving 8x + x2 = 3 + 6x Solving for variable 'x'. Reorder the terms: -3 + 8x + -6x + x2 = 3 + 6x + -3 + -6x Combine like terms: 8x + -6x = 2x -3 + 2x + x2 = 3 + 6x + -3 + -6x Reorder the terms: -3 + 2x + x2 = 3 + -3 + 6x + -6x Combine like terms: 3 + -3 = 0 -3 + 2x + x2 = 0 + 6x + -6x -3 + 2x + x2 = 6x + -6x Combine like terms: 6x + -6x = 0 -3 + 2x + x2 = 0 Factor a trinomial. (-3 + -1x)(1 + -1x) = 0Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-3, 1}
| 5x+4-3x=7x-8+11 | | y-2=1/2(x-(-4)) | | 218-178= | | 6x^3+15X^2+6x=0 | | 46.37*18.48= | | 2xy*x+3y= | | 6(x^2)+6x-44=0 | | 5(2x-6)=2(5-x) | | 3+4=-5+2 | | 3x+2=-5x+4 | | 4*(3+4x)=-18 | | 12d+7=6d+31 | | 13x+15-(x+2)= | | 5(a+7)=38 | | 47.2=9c-5 | | y=kx+10 | | 4e-7=9 | | 7p=21.7 | | 3x^2-16=2-3x | | 7e-9=26 | | 10q-5q+17-9= | | 7h+8g+2h+g= | | y=2(x+1) | | .11x+.08(165000-x)=15750 | | .11x+.08x(165000-x)=15750 | | (4x+3)+(3x+2)= | | h=-0.005t^2+0.6t+2 | | h=-0.005x^2+0.6t+2 | | h=0.005t^2+0.6t+2 | | 3x+1+3x+6= | | 8n+(5n+13)=7 | | 9x^3-105x^2-56x=0 |